2003
DOI: 10.1016/s0028-3932(02)00164-1
|View full text |Cite
|
Sign up to set email alerts
|

Memory orientation and success: separable neurocognitive components underlying episodic recognition

Abstract: Episodic recognition can be based on recollection of contextual details, on a sense of recent encounter, or some combination of the two. According to several cognitive models, selectively attending to these distinct aspects of memory may require different retrieval orientations and result in different neural responses depending upon whether or not retrieval is successful. Using event-related fMRI, we examined retrieval orientation by having subjects discriminate between two test words in one of two manners. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
216
6
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(284 citation statements)
references
References 60 publications
57
216
6
3
Order By: Relevance
“…Previous fMRI studies of recency memory have also reported greater activity in right BA 6/8 during recency memory tasks (Dobbins, Rice, Wagner, & Schacter, 2003;Dudukovic & Wagner, 2007). Moreover, Dudukovic and Wagner (2007) found that greater right BA 6/8 activity during correct recency decisions, versus correct novelty decisions; indicating that activity in this region is related to processes important for making correct recency judgments.…”
Section: Stimulus Number Manipulation: Right Lateral Premotor Cortexmentioning
confidence: 73%
See 3 more Smart Citations
“…Previous fMRI studies of recency memory have also reported greater activity in right BA 6/8 during recency memory tasks (Dobbins, Rice, Wagner, & Schacter, 2003;Dudukovic & Wagner, 2007). Moreover, Dudukovic and Wagner (2007) found that greater right BA 6/8 activity during correct recency decisions, versus correct novelty decisions; indicating that activity in this region is related to processes important for making correct recency judgments.…”
Section: Stimulus Number Manipulation: Right Lateral Premotor Cortexmentioning
confidence: 73%
“…Neuroimaging studies have highlighted the role of various PFC regions during temporal context retrieval (Cabeza, Anderson, Houle, Mangels, & Nyberg, 2000;Dobbins, Rice, Wagner, & Schacter, 2003;Dudukovic & Wagner, 2007;Konishi et al, 2002;Suzuki et al, 2002). However, it remains unclear which of these PFC activations are related to mediating domain or task-specific cognitive control processes such as, recollection-based retrieval monitoring, familiarity-based retrieval monitoring, retrieval success and establishing retrieval mode (Dobbins, Rice, Wagner, & Schacter, 2003;Nyberg et al, 1995;Yonelinas, Otten, Shaw, & Rugg, 2005) and which are related to mediating domaingeneral cognitive control processes including strategic ordering and controlled selection processes, to name a few (Moscovitch, 2002;Rajah & McIntosh, 2006;Rowe, Toni, Josephs, Frackowiak, & Passingham, 2000;Schumacher, Elston, & D'Esposito, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wagner et al (2005), following Rugg and colleagues' lead (e.g., Rugg & Wilding, 1996) pointed out that in at least some lateral parietal areas, activation tends to be greater when participants are required to retrieve information about the specific contextual details associated with an event, such as remembering which of two actions one performed in relation to a stimulus at encoding (Dobbins, 2003) or in which spatial location a stimulus was studied (Cansino et al, 2002; see also Hayes et al, 2004). This possibility also fits with classic interpretations of the heteromodal role of parietal cortex, in which it posited to act as a crossroads, integrating information from multiple sensory domains (Critchley, 1953).…”
Section: Current Theories Of the Lateral Parietal Region's Role In Mementioning
confidence: 96%